Coral restoration patents are disconnected from academic research and restoration practitioners - Roch, Cassandra; Schmidt-Roach, Sebastian; Duarte, Carlos M. (Frontiers in Marine Science, 2023)
Global warming and other anthropogenic impacts have driven coral reef degradation on a global scale to unprecedented levels of decline, with further dramatic deterioration predicted by the end of this century. Along with a drastic reduction in carbon emissions, we face an imperative to restore and maintain marine habitats to secure the ecosystem services they provide. While terrestrial systems have benefited from the agricultural revolution that provided industrial tools for effective habitat restoration, limited access to marine environments has inhibited similar levels of innovation resulting in a lack of cost-effective and scalable solutions. Commercial off-the-shelf technologies to cater to this growing industry are still absent. Here we conducted a systematic analysis of patent and scientific literature data as indicators of research and development output in the field of coral restoration. We identify technology growth trends, key areas of technological development and their geographical distribution. While the number of inventions filed for coral restoration is on the rise, similar to the published academic literature, the stakeholders leading both fields are unrelated. Academic research appears to lack translation into inventions for commercialization. Intellectual property protection further seems to be spearheaded by a few countries and is often limited in its application to national jurisdictions, with China dominating this sector. This does not mirror the distribution of current and need for coral restoration efforts globally. Here we discuss potential differences in cultural, socio-economic, and philosophical ideologies that drive these divergences and their impact as inhibitors or promoters of innovations targeting coral restoration solutions.